IMPLEMENTATION OF SMARTPHONE NAVIGATION FEATURES BY COMBINED FORCES IN DETERMINING THE HAZARDS OF TERRORISM IN POSO - Fitra, Mahturai Rian, Mrf; Runturambi, Arthur Josias Simon, Ajsr (Journal of Terrorism Studies, 2020)
The presence of armed terrorist groups in Poso can threaten security conditions in the country because their activities are considered quite dangerous for the surrounding community. This terrorist group did not hesitate to kill civilians who tried to deny its existence. Therefore, various joint military operations have been launched to crush this armed terrorist group, such as Camar Maleo and Tinombala. However, until now this terrorist group is difficult to destroy, due to the condition of the operating area in the form of dense tropical rainforest and steep slopes. This makes it difficult for troops to carry out chases and hunting. Through smartphone technology, troops can read operating field conditions much more easily and can predict far-field conditions in front of them more quickly. The concept used is the incorporation of raster data, vectors, and DEM which are processed using GIS (Geographic Information System) software with smartphone devices based on Android. The result is a smartphone device that has been inserted geospatial-based data used by troops in the operating field in the hunt for terrorists.